PRINCIPLES AND TENDENCIES IN PERFORMANCE OF PRENATAL DIAGNOSTICS: INTERNATIONAL EXPERIENCE AND POSSIBILITIES OF ITS APPLICATION - Vasilyevich Medvedev, Mikhail; Nikolaevich Suvorov, Georgiy; Mikhaylovich Osavelyuk, Aleksey; Sergeevich Zenin, Sergey; Ilinichna Suvorova, Ekaterina (Revista Inclusiones, 2020)
The relevance of this topic is based on the research on fundamental legal and medical postulates and the study of the sequence of trends in the regulation of prenatal diagnostics in systems of justice. This study is determined by the need for the application of this technology and its subsequent implementation in the Russian legal regulation. The purpose of this analysis is the projection of foreign legal maxima of this mechanism through the prism of national characteristics and, as a result, their adaptation to Russian realities. To achieve this goal, the authors have formulated the research objectives to identify legal principles and patterns of their occurrence, formation, development, and functioning in prenatal diagnostics of other states.